2022
DOI: 10.1213/xaa.0000000000001636
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Insensitivity and Thrombotic Risk Associated With Sequential Uses of Prothrombin Complex Concentrate and Andexanet Alfa for Apixaban Reversal During Acute Type A Aortic Dissection Repair: A Case Report

Abstract: The management of patients on direct oral anticoagulants (DOACs) who require emergent cardiac surgery is slowly evolving. The introduction of andexanet alfa, a novel antidote for apixaban and rivaroxaban, added a specific reversal agent to our armamentarium, but its safety and efficacy are still being investigated. We report 2 patients on DOAC treatment who required emergency cardiac surgery. Both received perioperative andexanet alfa together with prothrombin complex concentrate (PCC) at some time during 6 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
(18 reference statements)
0
0
0
Order By: Relevance
“…The following terms were used to search for relevant records: "andexanet alfa, " "heparin resistance, " "cardiopulmonary bypass, " and "cardiovascular surgery. " We finally detected nine cases of heparin resistance due to andexanet alfa, and those nine cases (in eight articles) were published as journal articles [7,9,[12][13][14][15][16][17]. Table 2 summarizes the characteristics of andexanet alpha-induced heparin resistance in 10 cases, including nine cases from the previous reports described above and one case from the present case report.…”
Section: Discussionmentioning
confidence: 84%
“…The following terms were used to search for relevant records: "andexanet alfa, " "heparin resistance, " "cardiopulmonary bypass, " and "cardiovascular surgery. " We finally detected nine cases of heparin resistance due to andexanet alfa, and those nine cases (in eight articles) were published as journal articles [7,9,[12][13][14][15][16][17]. Table 2 summarizes the characteristics of andexanet alpha-induced heparin resistance in 10 cases, including nine cases from the previous reports described above and one case from the present case report.…”
Section: Discussionmentioning
confidence: 84%
“…Several cases of Andexanet Alfa use in emergency cardiac surgery have been reported. 3,4 The Society of Thoracic Surgeons (STS), in their recent update to the Clinical Practice Guidelines on Patients Blood Management, recommended Andexanet Alfa administration in patients in need of emergent cardiac surgery with recent ingestion of DOAC. 5 Meanwhile, some patients received Andexanet Alfa before CPB showed heparin resistance and experienced CPB circuit thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 Meanwhile, some patients received Andexanet Alfa before CPB showed heparin resistance and experienced CPB circuit thrombosis. 3,4 The mechanism of heparin resistance due to Andexanet Alfa still needs to be fully understood. Prior study has suggested that Andexanet Alfa binds to the antithrombin-heparin complex and causes a lack of heparin-binding antithrombin.…”
Section: Discussionmentioning
confidence: 99%
“…No clinical trials have reported the efficacy of andexanet alfa in cardiac surgery with CPB, and its clinical use is based on the experience reported in several case reports [4][5][6][7]. These reports often describe heparin resistance following administration of andexanet alfa before CPB, as andexanet alfa also binds to the heparin-antithrombin complex and neutralizes its anticoagulant effect [2].…”
Section: Discussionmentioning
confidence: 99%